PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING BERBANTU MEDIA VISUAL TERHADAP HASIL BELAJAR - Afida Desta Afifa; Sutrisni Andayani; Jazim Ahmad (Universitas Muhammadiyah Metro, 2024)
This study aims to determine whether there is an effect of reciprocal teaching learning models assisted by visual media on learning outcomes and to find out which learning outcomes are higher between student learning outcomes using the reciprocal teaching learning model assisted by visual media or conventional learning models assisted by visual media. The research method used in this study was a quasi-research with a non-equivalent form of control group design. Collecting data in this study using test questions. The results of this study indicate that there is an effect of the reciprocal teaching learning model, this can be seen in the calculation of the paired sample t-test, which is 0.029 <0.05. In addition, the average mathematics learning outcomes of students who use the reciprocal teaching learning model with visual media is higher than the average mathematics learning outcomes of students who use conventional learning models with visual media, this can be seen in the calculation of the independent test sample t-test, namely 0.015<0.05.